Current Evidence and Potential Mechanisms of Therapeutic Action of PEDF in Cervical Cancer Treatment - Han, J.; Guo, J. (Current Molecular Medicine, 2015)
Cervical cancer is the second leading gynecological malignancy threat to the health of women in the world. However, few improvements in the efficacy of treatments of cervical cancer have been reported for the recurrent and metastasis patterns. As an endogenous antitumor agent, pigment epithelium derived factor (PEDF) has attracted wide attention, and its sensitivity to estrogen suggests a special role in female tumors, including cervical cancer. This review aims to summarize recent findings, the role of PEDF in cervical cancer treatment, and enhance the current understanding of the antitumor properties of PEDF such as inhibiting angiogenesis and metastasis, inducing tumor cell apoptosis and differentiation, and modulating cellular immunity against cervical cancer. The production and delivery of PEDF, as well as derived short peptides and their respective receptors will also be discussed.
Keywords: metastasis